Prognostic significance of AMPK activation in advanced stage colorectal cancer treated with chemotherapy plus bevacizumab - Zulato, E (Nature Publishing Group, 2014)
BACKGROUND: AMP-activated protein kinase (AMPK) has a central role in cellular energy sensing and is activated in preclinical tumour models following anti-vascular endothelial growth factor (VEGF) therapy. The possible predictive or prognostic role of AMPK status in cancer patients treated with anti-VEGF drugs has not been investigated so far. METHODS: Expression of components of the AMPK pathway including phosphorylated AMPK (pAMPK), phosphorylated acetyl-Coa carboxylase (pACC) and liver kinase B1 (LKB1) was investigated by immunohistochemistry in 48 colorectal cancers treated with FOLFIRI plus bevacizumab. Correlation between pAMPK and pACC and associations between the AMPK pathway scores and clinico-pathological characteristics were assessed. Overall survival (OS) was estimated through Kaplan–Meier method, whereas hazard ratios were computed to identify prognostic factors. RESULTS: Fourteen patients (29.2%) were included in the pAMPK-negative group (score ⩽5), whereas 34 patients (70.8%) were included in the pAMPK-positive group (score >5). The Spearman's coefficient for the correlation between pAMPK and pACC scores in primary tumour samples was 0.514 (P=0.0002). Low pAMPK levels were associated with worse OS (P-value 0.0002) but not with PFS, whereas low pACC levels were associated both with worse OS and PFS (P-value 0.0007 and 0.01, respectively). CONCLUSIONS: Our findings suggest that high tissue AMPK activation is a prognostic biomarker in this cohort of metastatic colorectal cancer patients.